Effects of manganese and other agents on the calcium uptake that follows depolarization of squid axons - Baker, P. F. (1973)
1. The Ca-sensitive photoprotein aequorin was injected into squid axons and the light response to stimulation or depolarizing voltage clamp pulses recorded. 2. The effects of Mn(2+), Co(2+), Ni(2+), La(3+) and of the organic Ca antagonists D-600 and iproveratril on the early tetrodotoxin-sensitive and late tetrodotoxin-insensitive components of the light response were studied. 3. The late tetrodotoxin-insensitive component can be blocked, reversibly, by concentrations of Mn, Co and Ni that reduce but do not block the tetrodotoxin-sensitive component. The late component can also be blocked by La(3+) and the organic Ca antagonists D-600 and iproveratril. 4. Mn(2+), Co(2+), Ni(2+) and the drug D-600 all reduce the Na currents, but have little effect on either outward or inward K currents. Tetraethylammonium blocks the outward K current but has no appreciable effect on the tetrodotoxin-insensitive entry of Ca. 5. Concentrations of Mn between 5 and 50 mM substantially reduce the light output during a train of action potentials; they also slightly reduce the rate of rise of the action potential. 6. On pharmacological grounds it is concluded that the tetrodotoxin-insensitive component of Ca entry does not represent Ca ions passing through the K permeability channels. There must exist a potential-dependent late Ca channel that is distinct from the well known Na and K channels of the action potential. A possible function for this late Ca channel in the coupling of excitation to secretion is discussed.